O potrzebie jednolitości koncepcji strony postępowania administracyjnego - Adamiak, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The complexity of the regulations of substantive administrative law, which is directly related to procedural administrative law, makes it impossible to adopt a uniform concept of locus standi of a party in administrative proceedings. The fact that administrative proceedings are based on an ex officio principle and the principle of accusatorial procedure is already an element which makes it necessary to adopt different solutions depending on whether it is a case of initiation ex officio or initiation by application. However, the above applies only to determination of legal interest, without deciding on the full duty of public administration body to provide the legal entity with the administrative rights of defense under legal regulations.A strict interpretation of the law that defines the legal interest of an individual causes lack of durability of administrative decisions. An unfounded deprivation of the rights of defense in the course of ordinary proceedings causes a repeated undertaking of defense in the course of extraordinary administrative proceedings, which prolongs the final settlement of the case. Thus, for the stability of not only the rights or obligations of an individual but also an execution of the tasks in accordance with the law, the interpretation of the law, which takes into account the constitutional principle of a democratic state of law granting the right to a trial, is of paramount importance.
Keywords: postępowanie administracyjne; strona postępowania; jednolitość koncepcji